A GRASP approach to the container-loading problem - Moura, Ana (2013)
The GRMODGRASP, a new algorithm for the container-loading problem (CLP) based on the greedy randomized adaptive search procedure (GRASP) approach, is discussed. Based on a wall-building, constructive heuristic, it can achieve high levels of cargo stability without compromising the container's volume use. The algorithm builds a solution, and then it improves the solution with a local-search algorithm. If it finds a better solution, this new solution replaces the old and a new neighborhood is built around it. The algorithm uses a first better strategy when more than one better solution exists